NAC transcription factor family genes are differentially expressed in rice during infections with Rice dwarf virus, Rice black-streaked dwarf virus, Rice grassy stunt virus, Rice ragged stunt virus, and Rice transitory yellowing virus - Nuruzzaman, Mohammed; Sharoni, Akhter Most; Satoh, Kouji; Karim, Mohammad R.; Harikrishna, Jennifer A.; Shimizu, Takumi; Sasaya, Takahide; Oomura, Toshihiro; Haque, Mohammad A.; Kikuchi, Shoshi (Frontiers in Plant Science, 2015)
Expression levels of the NAC gene family were studied in rice infected with Rice dwarf virus (RDV), Rice black-streaked dwarf virus (RBSDV), Rice grassy stunt virus (RGSV), Rice ragged stunt virus (RRSV) and Rice transitory yellowing virus (RTYV). Microarray analysis showed that 75 (68%) OsNAC genes were differentially regulated during infection with RDV, RBSDV, RGSV, and RRSV compared with the control. The number of OsNAC genes upregulated was highest during RGSV infection, while the lowest number was found during RTYV infection. These phenomena correlate with the severity of the syndromes induced by the virus infections. Most of the genes in the NAC subgroups NAC22, SND, ONAC2, ANAC34, and ONAC3 were down-regulated for all virus infections. These OsNAC genes might be related to the healthy stage maintenance of the host plants. Interestingly, most of the genes in the subgroups TIP and SNAC were more highly expressed during RBSDV and RGSV infections. These results suggested that OsNAC genes might be related to the responses induced by the virus infection. All of the genes assigned to the TIP subgroups were highly expressed during RGSV infection when compared with the control. For RDV infection, the number of activated genes was greatest during infection with the S-strain, followed by the D84-strain and the O-strain, with seven OsNAC genes upregulated during infection by all three strains. The Os12g03050 and Os11g05614 genes showed higher expression during infection with four of the five viruses, and Os11g03310, Os11g03370, and Os07g37920 genes showed high expression during at least three viral infections. We identified some duplicate genes that are classified as neofunctional and subfunctional according to their expression levels in different viral infections. A number of putative cis-elements were identified, which may help to clarify the function of these key genes in network pathways.